2016
DOI: 10.1007/s13277-016-5128-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of withasteroids: withametelin induces cell cycle arrest at G2/M phase and mitochondria-mediated apoptosis in non-small cell lung cancer A549 cells

Abstract: Considerable interest has been gained by withasteroids because of their structural uniqueness and wide spectrum of biological activities. However, limited systematic studies for proving their cytotoxic potential have so far been reported. Hence, an attempt was made to test the cytotoxicity of six withasteroids viz., withametelin (WM), withaphysalin D, withaphysalin E, 12-deoxywithastramonolide, Withaperuvin B, and physalolactone against A549, HT-29, and MDA-MB-231 cancer cell lines. Significant cytotoxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
2
14
0
2
Order By: Relevance
“…Its apoptosis was based on annexin V/PI analysis and reached to about 20% for annexin V positive. In contrast, several drugs were reported to G2/M arrest and apoptosis without detectable subG1 accumulation, such as erianin in human osteosarcoma cells, evodiamine in lung cancer H446 and H1688 cells, withametelin in lung cancer A549 cells, and diarylpyrazole derivative (AM251) in A375 cells . Similarly, we found that sinularin induced G2/M arrest and apoptosis without detectable subG1 accumulation in oral cancer cell at 24 h treatment, where the apoptosis was confirmed by flow cytometry (annexin V/PI and pancaspase analyses) and western blotting (caspases 3, 8, 9, and PARP).…”
Section: Discussionsupporting
confidence: 52%
“…Its apoptosis was based on annexin V/PI analysis and reached to about 20% for annexin V positive. In contrast, several drugs were reported to G2/M arrest and apoptosis without detectable subG1 accumulation, such as erianin in human osteosarcoma cells, evodiamine in lung cancer H446 and H1688 cells, withametelin in lung cancer A549 cells, and diarylpyrazole derivative (AM251) in A375 cells . Similarly, we found that sinularin induced G2/M arrest and apoptosis without detectable subG1 accumulation in oral cancer cell at 24 h treatment, where the apoptosis was confirmed by flow cytometry (annexin V/PI and pancaspase analyses) and western blotting (caspases 3, 8, 9, and PARP).…”
Section: Discussionsupporting
confidence: 52%
“…Although, we could not confirm an increase for subG1 population, sinularin induced apoptosis in breast cancer cells as validated by annexin V/7AAD, pancaspase analyses and Western blotting. Drugs such as evodiamine [ 28 ], withametelin [ 29 ], and (−)-anonaine [ 30 ], also cause apoptosis without subG1 accumulation. Interestingly, the proportion of drug-induced apoptotic cells may change over time for subG1 accumulation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability assays of UACC 903 cells transfected with siRNA, and melanoma cells (UACC 903, 1205 Lu, C8161.CI9, MelJuSo), normal human fibroblasts (FF2441), and melanocytes (NHEM) treated with ALDH inhibitors were performed as described previously (43)(44)(45). Briefly, 5,000 cells per well were plated in a 96-well plate and incubated overnight at 37 C in a 5% CO 2 atmosphere.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…To quantify ROS levels, the nonfluorescent dye DCFDA (Sigma) was used (43). DCFDA turns to highly fluorescent 2 0 ,7 0 -dichlorofluorescein upon oxidation by ROS generated in cells (43). Briefly, cells were treated with 5 mmol/L of ALDH inhibitor or DMSO for 24 hours.…”
Section: Ros Assaymentioning
confidence: 99%
See 1 more Smart Citation